Kajian Empiris Pengaruh Diversitas Dewan Direksi Terhadap Kinerja Perbankan Di Indonesia - Erna Chotijah Suhatmi; Tri Irawati; Suhesti Ningsih (Jurnal Akuntansi dan Pajak, 2025)
Users always look forward to financial reports, especially from banks. This is intended to see an overview of information on the development of profits for the companies being observed. Gender, ethnicity, educational background, age and proportion of the board of directors in a company are identical to board diversity. This study aims to determine the relationship between board diversity and banking performance in Indonesia. This study uses a descriptive analytical method. Secondary data used in this study are the financial reports of banking companies listed on the Indonesia Stock Exchange from 2016 to 2022. The data analysis method used in this study is multiple regression analysis. The dependent variable in this study is company performance as reflected in the return on assets while the independent variables in this study are board gender diversity and board expertise diversity. Based on the simultaneous test seen from the probability F value of 0.01 or less than the alpha value of 0.05, then together board gender diversity and board expertise diversity have an effect on return on assets in banking companies. The partial test on the t-test indicates that the value of the BGD variable has an effect on ROA in banking companies. This is indicated by a probability value of 0.003 or less than the alpha value of 0.05. The results of the study also stated that the regression coefficient value of BGD is positive 0.108. In addition, the results of the study showed the influence of BED on ROA of banking companies. This can be shown in the probability results of BED less than the alpha value of 5%, which is 0.005. In addition, the regression coefficient value of BED also shows a positive relationship of 0.129.